Can European Banks Survive a Unified Currency in a Nationally Segmented Capital Market? - Jan A. Kregel (Levy Economics Institute of Bard College, 2000)
The euro was expected to become a substitute for the U.S. dollar as an international currency. However, compromises made during its creation make it a less than perfect substitute in the medium term. Among these compromises was the application of macro convergence and micro diversity in financial markets and supervision at the national level. This now prevents the creation of a unified capital market and places EU banks at a disadvantage when competing with U.S. banks in global markets. There were also peculiarities in the integration process that led to a single currency in the United States that suggest further institutional changes will be necessary.
Keywords: 330